Assessing Secondary High School Student Needs for Descriptive Texts Concerning Climate Change - Tasyaa, Nabilla; Inderawati, Rita; Mirizon, Soni (VELES Voices of English Language Education Society, 2023)
Addressing Indonesia's vulnerability to climate-related disasters, this study explores the development of English reading materials on climate change for secondary high school students. The goal is to tailor these materials to the students' specific needs, considering their English proficiency levels and the challenges they face in reading comprehension. Through a mixed-method approach involving questionnaires and semi-structured interviews, the study captures insights from students, English teachers, and stakeholders. The findings highlight the critical role of English in students' future careers. However, most students are beginners in English, and they experience significant difficulties in understanding reading materials. There is a clear need for descriptive texts that are accessible at their English level and integrate climate change topics relevant to their context. The study identifies a gap in current educational resources, emphasizing the necessity of incorporating climate change content in a manner that both informs and is comprehensible to students. In conclusion, this study advocates for the creation of supplementary descriptive texts about climate change, customized to align with the students' linguistic abilities and educational curriculum. This initiative aims not only to enhance students' English skills but also to increase their awareness and understanding of crucial environmental issues.